1981
DOI: 10.1145/322234.322242
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing Tasks with Exponential Service Times to Minimize the Expected Flow Time or Makespan

Abstract: The problems of minimizing the expected makespan and minimizing the expected tic for a finite set of independent tasks with exponential service-time distributions on m ~ 2 it processors are considered. It is shown that a scheduling policy minimizes the expected flow timq only if it is shortest expected processing time tint, and that a policy minimizes the expected make and only if it is longest expected processing time fast. rE,,' WORDS ArCD PHRASES: scheduling, flow time, makespan, sequencing, policy C R CATE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 4 publications
1
82
0
Order By: Relevance
“…On the other hand, it reduces to the nonpreemptive shortest expected processing time (Sept) policy when the hazard rate is increasing. The optimality of this static policy, Sept, has been shown earlier for exponentially distributed processing times by Glazebrook [11], Weiss and Pinedo [42], and Bruno et al [2]. In the case when processing times are not drawn from a distribution with monotone hazard rates, Coffman et al [6] have shown that this policy is not optimal, even if all processing times follow the same two-point distribution and even if we deal with only two processors.…”
Section: Previous Workmentioning
confidence: 72%
See 1 more Smart Citation
“…On the other hand, it reduces to the nonpreemptive shortest expected processing time (Sept) policy when the hazard rate is increasing. The optimality of this static policy, Sept, has been shown earlier for exponentially distributed processing times by Glazebrook [11], Weiss and Pinedo [42], and Bruno et al [2]. In the case when processing times are not drawn from a distribution with monotone hazard rates, Coffman et al [6] have shown that this policy is not optimal, even if all processing times follow the same two-point distribution and even if we deal with only two processors.…”
Section: Previous Workmentioning
confidence: 72%
“…If processing times are exponentially distributed and release dates are absent, F-Gipp coincides with the preemptive Wsept rule. As mentioned above, this classical policy is optimal if all weights are equal (Glazebrook [11], Weiss and Pinedo [42], Bruno et al [2]) or, more generally, if they are agreeable (Kämpke [13]). If there is only a single machine available and jobs have arbitrary release dates, then F-Gipp coincides with preemptive Wsept and is optimal (Pinedo [25]).…”
Section: Our Contributionmentioning
confidence: 99%
“…Instead, literature reflects a variety of research on restricted problems as those with special probability distributions for processing times or special job weights [1,29,19,5,9,30].…”
Section: Definition 1 a (Online) Stochastic Policymentioning
confidence: 99%
“…If processing times are exponentially distributed and release dates are absent, our policy coincides with the Weighted shortest expected processing time (WSEPT) rule. This classical policy is known to be optimal if all weights are equal [1] or, more general, if they are agreeable, which means that for any two jobs i, j holds that [9]. If only one machine is available, we solve the weighted problem 1 | pmtn | E [ w j C j ] optimally by utilizing the Gittins index priority policy [11,24,30].…”
Section: Definition 1 a (Online) Stochastic Policymentioning
confidence: 99%
“…For example, the rule shortest expected processing time first (SEPT), i.e., schedule jobs in order of non-decreasing expected processing times, is known to be optimal for many variants, see, e.g., [21], [29], [3], [11], and [28]. Moreover, for the weighted single-machine problem, the rule weighted shortest expected processing time first (WSEPT) is optimal [18].…”
Section: Introductionmentioning
confidence: 99%